Effect of Grain Size on the Corrosion Behavior of TiAlBN Nanocomposite Coating - Mohd Rosli, ZULKIFLI; Kwan, Wai Loon; Jariah, Mohamad Juoi; nafarizal, nayan; Zainab , Mahamud (2012)
TiAlBN nanocomposite coating have been deposited by varying nitrogen-to-total gas flow rate ratio (RN) of 5, 15, 20, 25%, and varying substrate temperature of 100, 200, 300, and 400 °C. The coating was deposited on AISI 316 substrates using radio frequency (RF) magnetron sputtering with single Ti-Al-BN hot-pressed target. The crystallographic phase, structural, and grain size was evaluated using glancing angle X-ray diffraction analysis (GAXRD). The corrosion behavior of the coating was determined using potentiodynamic polarization test. The grains size of the deposited coating (calculated using Scherrer’s formula) were found to be in the range of 3.5 to 5.7 nm. It was also found that the grain size affects the corrosion behavior of the coating in which larger grain size decreases the corrosion resistance of the deposited TiAlBN nanocomposite coating. In addition, it was observed that the corrosion resistance of the coating is lower than the substrate material. Nevertheless, the coating was able to protect the surface of the uncoated AISI 316 substrate from pitting corrosion. Moreover, the coating exhibited a corrosion resistance comparable with other high corrosion resistance coatings such as (Ti,Al)N, and TiAlSiN.